PANEER WHEY BASED JELLY CONFECTION - P. K. WASNIK; S. P. CHANGADE (The Bioscan, 2015)
Paneer whey testing 6.36% total solids was used at different levels viz., 0% (T1), 25% (T2), 50% (T3), 75% (T4) and 100% (T5) with colour (0.1%), flavour (0.2%), citric acid (1%), high methoxyl pectin (1.5%) and ground sucrose (47.5%) for making jelly confection. Mixture of each treatment was concentrated till reaches to 65°Brix and allowed to set in sterilized stainless steel circular moulds at 28-32°C. Intact jelly mass was cut manually into 2×0.7×0.8 cm3 size pieces and twist wrapped manually in polypropylene wrappers. Highest overall acceptabil- ity score (7.48±0.71) was allotted to treatment T3. Optimized product obtained using 50% paneer whey. Paneer whey was acceptable up to 100% replacement of water without adversely affecting sensory quality of the product. Results showed scope for enhancing nutrients level of jelly confection, economic benefit to the dairy plants through utilization of whey at its production point mitigating whey disposal and environmental pollution problems